First International Electronic Conference on Nutrients, Microbiota and Chronic Disease 2020
DOI: 10.3390/iecn2020-06995
|View full text |Cite
|
Sign up to set email alerts
|

Aging Effects on Gut Microbiota in SAMP8 Mice

Abstract: We have studied the effects of aging on the fecal microbiota composition in the senescence-accelerated prone mice SAMP8 strain. We compared animals two, four, and six months old. Feces were collected at the end of each period and a genomic study was carried out on fecal DNA using the Illumina MiSeq analyzer. The Shannon diversity index showed similar values along this period and the number of species was neither affected by aging. The phylum Verrucobacteria went up with age, showing a seven-fold increase at si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Changes in the composition of the gut microbiota coextensive with aging likely contribute to immunosenescence and to the development of a pro-inflammatory phenotype [ 69 ]. In fact, SAMP8 mice at 6 months of age, showed a reduction in probiotic species, while the proinflammatory species of the intestinal microbiota increased [ 70 ]; these are able to secrete bacterial amyloids and lipopolysaccharides that are considered neurotoxic [ 71 ]. Moreover, SDP increases the presence of bacterial families that enhance the intestinal barrier function, as well as the growth of species that are well-known mediators of anti-inflammatory and tolerogenic responses [ 23 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the composition of the gut microbiota coextensive with aging likely contribute to immunosenescence and to the development of a pro-inflammatory phenotype [ 69 ]. In fact, SAMP8 mice at 6 months of age, showed a reduction in probiotic species, while the proinflammatory species of the intestinal microbiota increased [ 70 ]; these are able to secrete bacterial amyloids and lipopolysaccharides that are considered neurotoxic [ 71 ]. Moreover, SDP increases the presence of bacterial families that enhance the intestinal barrier function, as well as the growth of species that are well-known mediators of anti-inflammatory and tolerogenic responses [ 23 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the neuronal protective effects of SDAP were attributed to its effects on the gut in two other publications [5,83] by this same research group, which demonstrated that aging in mice induces mild-grade inflammatory changes and that senescence promotes an increase in populations of potentially pathogenic microorganisms, with a reduction in microorganisms with probiotic potential (Lactobacillus hayakitensis and Blautia hansenii) that promote protection against infections by Clostridium spp. In this study [83], supplementation of SDAP reversed such deleterious changes in the aging animals, promoting an effective response to an intestinal challenge.…”
Section: Sdap In Aging Animalsmentioning
confidence: 99%